A constituição do sistema participativo de garantia Sul de Minas e sua contribuição para a Agroecologia na região - Hirata, Aloísia Rodrigues (2016)
In Brazil, the law establishes that organic products must be produced without using pesticides, chemical fertilizers or synthetic substances harmful to the environment, and the process should consider the responsible use of soil, water, air and other natural resources, respecting environmental, social and cultural relations. To market produce as organic, the law requires such products to be officially certified by the Conformity Assessment Body (OAC) . The assessment can also be done by audit firms or a Participative Conformity Assessment Body (OPAC). In the south of Minas Gerais, Brazil, by means of an extension project coordinated by the Federal Institute of Southern Minas Gerais (IFSULDEMINAS) in partnership with the Technical Assistence and Rural Extension Company (EMATER-MG) and supported by the Ministry of Agriculture, Livestock and Supply (MAPA), it was possible to constitute the Organic Producers Association Center of Southern Minas Gerais (OSM) in 2012, bringing together farmers from eleven entities, which, along with partners, have managed to create the Participatory Guarantee System (SPG Southern Minas Gerais ) and accredit the first OPAC in Minas Gerais. Faced with this scenario, the study aimed to rescue the constitution process of the SPG South of Minas, identify how the process of credibility generation occurs regarding the conformity assessment, and verify the contributions of SPG South of Minas to strengthen agroecology in the region. The work was conducted with five associations and two cooperatives associated with OSM. As a research with qualitative approach, we performed document analysis, consisting of the identification and assessment of main documents obtained from OPAC South of Minas. All social conviviality with the groups was used as participant observation (pair and verification visits, reunions and meetings). The focus group interview, another methodological technical procedure, was conducted with five groups from three different associations, allowing information and reflections regarding the process of credibility generation. Among the results obtained, we emphasized that the implementation of the SPG South of Minas was favored by the existing social capital in several organizations that make up the network, as well as by the involvement of partner public institutions. However, the need to develop a participation culture to strengthen social relations and trust between the groups and the system is needed. Another relevant factor identified concerns the procedures and methodology for conformity assessment, which has guaranteed the involvement of everyone in the process, providing greater t ransparency and enabling the construction of agroecologic knowledge by means of experience exchanges and knowledge valuations. Finally, this work showed the actions that the SPG South of Minas has developed, which have contributed to the agroecology in the region, as Southern Circuit of Agroecology in Minas Gerais, the trade of organic products, the work with native seeds and the influence of this network over the actions of partner institutions, especially with the creation of a study group in Agroecology, Raiz do Campo, at the Inconfidentes campus in IFSULDEMINAS.